Cellular Blue Nevomelanocytic Lesions: Analysis of Clinical, Histological, and Outcome Data in 37 Cases. (July 2016) - Hung, Tawny; Argenyi, Zsolt; Erickson, Lori; Guitart, Joan; Horenstein, Marcelo G.; Lowe, Lori; Messina, Jane; Piepkorn, Michael W.; Prieto, Victor G.; Rabkin, Michael S.; Schmidt, Birgitta; Selim, Maria A.; et al.
Abstract : Abstract: Cellular blue nevomelanocytic lesions (CBNLs) frequently pose diagnostic problems to pathologists, and their biological potential may be difficult to establish. In this study, the authors have analyzed the clinical, histological, and outcome data of 37 cellular blue nevomelanocytic lesions and the molecular characteristics of 4 lesions. The cohort of cases comprised 8 cellular blue nevi (CBNs), 17 atypical cellular blue nevi (ACBNs), and 12 blue-nevus–like melanomas (BNLMs) with a mean follow-up of 5 years. The average age at diagnosis was 25.9 years for patients with ACBN, versus 30.4 years for CBN, and 44.6 years for BNLM. Both CBN and ACBN occurred most frequently on the trunk or extremities, whereas BNLM primarily involved the scalp. Histologically, CBN and ACBN were characterized by a mean diameter of <1 cm, absence of necrosis, low mitotic rate (mean: 1–2 mitotic figures/mm 2 ), little or no infiltrative properties, and usually low-grade cytologic atypia. In contrast, BNLM had a mean diameter of 1.6 cm, necrosis, tissue infiltration, greater mitotic activity (mean: 6 mitotic figures/mm 2 ), and high-grade cytologic atypia. ACBNs often were larger, more densely cellular, exhibited higher mitotic counts, and were cytologically more atypical than CBN. Seven CBN cases with follow-up had a benign clinical course (average follow-up of 4.7 years). Among 6 patients with ACBN who underwent sentinel lymph node (SLN) biopsy, 3 were positive, and a single additional case had 1 positive non-SLN (this patient did not have a SLN biopsy performed). All 14 cases of ACBN with follow-up were alive and without recurrence with mean follow-up of 5 years. Of the 9 melanoma cases with follow-up, 3 patients with SLN and non-SLN involvement died from their disease (average follow-up of 4.8 years). Array comparative genomic hybridization was performed on 2 ACBNs and 1 BNLM: One of the 2 ACBNs showed chromosomal aberrations and 1 BNLM showed multiple chromosomal gains and losses. Multiplex polymerase chain reaction was performed on 1 ACBN, and no mutations were found. From these results, the authors conclude that ACBN occupy an intermediate position within the spectrum of CBN and BNLM, yet many lesions cannot be reliably distinguished from either CBN or BNLM because of overlapping histologic features. However, in general, ACBNs seem to aggregate more closely with CBN in terms of clinical, histological, molecular profile (limited data), and biological behavior.